The Analysis of Urban Adolescents’ Reception of Pornography on Social Media - Nur Kholisoh; Rajab Ritonga; Melly Ridaryanthi (Ikatan Sarjana Komunikasi Indonesia, 2022)
There are many pornographic sites on social media nowadays. In 2018, The Indonesian Child Protection Commission found that 91.58% of 6,000 adolescents had been exposed to pornography. Adolescents are those in the age group that is very vulnerable to the effects of pornography. This study aims to identify and examine urban adolescents’ reception of pornography on social media. The selection of urban adolescents as research objects was because they have easier access to social media than other age groups. The sample of this research was taken from adolescents in DKI Jakarta and Surabaya considering that these two cities are among the six cities with the highest number of adolescents in Indonesia. This study uses the reception theory presented by Stuart Hall who suggests that audiences can play an active role in decoding messages. In addition, this study employs a constructivist paradigm with a qualitative approach. The method used was the reception analysis which focuses on production, text, and audience in a framework that can be utilized to analyze the relationship of each element. The informants in this study were adolescents in DKI Jakarta and Surabaya who were aged between 15 and 19 years. Informants' preference was conducted purposively by considering variations based on social and cultural context backgrounds. The results showed that all the informants had watched pornography on social media, either intentionally or not. In addition, four out of ten informants are in an Oppositional Position for rejecting messages conveyed in pornographic broadcasts on social media. Meanwhile, six other adolescents are in a Negotiated Position, where they disagree with pornography on social media but can accept the meaning of pornography because it satisfies their curiosity.